Rapid diagnosis of respiratory syncytial virus infections in immunocompromised adults. - Englund, J A (1996)
Although rapid antigen detection methods for the documentation of respiratory syncytial virus (RSV) infections are widely used with pediatric patients, these tests have not been prospectively evaluated in immunocompromised (IC) adults. For bone marrow transplant recipients and adult patients undergoing chemotherapy for leukemia who had recent onset of respiratory symptoms, respiratory samples (combined nasal wash [NW]-throat swab [TS], endotracheal tube [ET] aspirate, or bronchoalveolar lavage [BAL] samples) were collected for simultaneous culture and rapid antigen detection with the Directigen test kit (Becton Dickinson, Cockeysville, Md.). NW specimens from hospitalized pediatric patients with suspected RSV infection were also evaluated. Viral quantitation was performed on aliquots of the original specimens. A total of 539 samples from 372 adult patients were evaluated. RSV was isolated from 56 specimens (40 NW-TS, 7 ET aspirate, and 9 BAL specimens). By using culture as the "gold standard," rapid antigen detection had a sensitivity of 15% for adult NW-TS specimens, 71.4% for ET aspirate specimens, and 88.9% for BAL specimens; the specificity was > or = 97% for all specimen types. Significantly greater viral quantities were present in pediatric NW specimens than in adult NW specimens. In adults, more virus was present in BAL and ET aspirate specimens than in NW-TS specimens. Rapid detection of antigen respiratory samples obtained from the lower respiratory tracts of IC adults is sensitive and specific, but detection in upper respiratory tract samples is insensitive. The lower sensitivity of antigen detection in NW-TS specimens may be due to decreased viral load. A BAL specimen is more sensitive than an NW-TS specimen for the rapid diagnosis of RSV disease in IC adults.